Controle químico de Stachys arvensis L. e doenças fungicas em trigo associado a diferentes doses de Orobor - Coradini, Cezar (2013)
Weeds and fungal diseases interfere negatively in wheat development, yield and grain quality, and chemical control method is the most widespread among producers. In order to evaluate the contribution of the adjuvant Orobor in the performance of metsulfuron methyl herbicides (Ally 600 WG), iodosulfuoron methyl (Hussar WG) and 2,4-D (amino SL) (Experiment I) and fungicides epoxiconazol (Opus 125 SC ), pyraclostrobin (Comet EC 250) and Opera SE (50 g L-1 epoxiconazol + 133 g L-1 pyraclostrobin) (Experiment II) in wheat two field experiments were conducted in the 2012 crop season. In Experiment I (Santa Maria, RS), the experimental design used was a randomized block in factorial arrangement (3 x 5) + 1, with four replications. Factor A was composed of the herbicide metsulfuron methyl (Ally - 6.6 g ha-1 plus Assist 0.1% v/v in the absence of Orobor) iodosulfuoron methyl (Hussar - 70 g ha-1 plus Hoefix 0.3% v/v in the absence of Orobor) and 2,4-D amine (amino - 0.75 L ha-1) and factor B was composed of Orobor doses (0, 50, 100, 150 and 200 mL ha -1). Additional treatment was represented by control. The results indicate that the application of Orobor (50, 100, 150, 200 mL ha-1) in combination with metsulfuron methyl (6.6 g ha-1) methyl iodosulfuoron (70 ha-1) and 2,4-D (0.75 L ha-1) applied in post-emergence of wheat, exhibit different behavior regarding the control of Stachys arvensis (auricula) and on other variables related to the production system. Only iodosulfuoron methyl (70 ha-1) increased in the control of this weed when associated with Orobor (100 and 150 mL ha-1). It also demonstrated that the better performance of iodosulfuoron methyl resulted in no benefits for wheat (test weight and grain yield). Hence the need to expand research for this adjuvant (Orobor) with herbicides. In Experiment II (Itaara, RS) the experimental design was also a randomized block in factorial arrangement (3 x 5) + 1, with four replications. Factor A was fungicides epoxiconazol (Opus 125 SC - 0.75 L ha-1), pyraclostrobin (Comet EC - 0.80 L ha-1) and the mixture of epoxiconazol (50 g L-1) + pyraclostrobin (133 g L-1) (Opera SE - 1.0 L ha-1) and factor B was adjuvants Assist (500 mL ha-1) and Orobor (0, 50, 100 and 150 mL ha-1). Additional treatment was also represented by control. The results demostrated that the fungicidal mixture or epoxiconazole epoxiconazole with pyraclostrobin better control leaf spots, regardless of the adjuvant being Assist (500 mL ha-1) or Orobor (50 to 100 mL ha-1) for the mixture of epoxiconazole and pyraclostrobin . Adding Orobor at doses above 100 mL ha-1 for the mixture of epoxiconazol with pyraclostrobin did not increase the control of leaf spots. The addition of 50 mL ha-1 in solution containing Orobor in the mixture containing epoxiconazol or the pyraclostrobin-epoxiconazol mixture reduces giberelados grain and increases wheat grain yield. In the applied doses, epoxiconazol, pyraclostrobin and the mixture of pyraclostrobin with epoxiconazol did not negatively affect test weight (PH), grain weight (PMG) and wheat yield. Additional studies with Orobor (50 and 100 mL ha-1) added to the sprays containing herbicides and fungicides are needed to confirm these results.